2006
DOI: 10.1002/ch.314
|View full text |Cite
|
Sign up to set email alerts
|

Stress reducing regulative effects of integrated mental training with self‐hypnosis on the secretion of dehydroepiandrosterone sulfate (DHEA‐S) and cortisol in plasma: a pilot study

Abstract: Early observations have shown that preventive educational efforts towards experience of stress entail advantages in terms of improved well-being, health and performance. We examined the influence in healthy subjects of self-hypnosis and mental training taught in group sessions, with individual training in between according to a standard protocol, and integrated in daily life and work for six months, on the alteration in plasma concentration of the stress hormone cortisol and the 'anti ageing' hormone dehydroep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
(39 reference statements)
0
7
0
5
Order By: Relevance
“…Increased level of DHEA has been observed (McCraty et al, 1998) as an effect of an emotional self-management program that required participant to focus on feelings of care for others. Another study showed that a mental training program was successful in changing in DHEA-S (Johansson & Uneståhl, 2006). Recovery from severe stress appears to be facilitated by DHEA; an effective coping predicted higher plasma DHEA levels (Yehuda et al, 2006).…”
Section: Neurobiological Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Increased level of DHEA has been observed (McCraty et al, 1998) as an effect of an emotional self-management program that required participant to focus on feelings of care for others. Another study showed that a mental training program was successful in changing in DHEA-S (Johansson & Uneståhl, 2006). Recovery from severe stress appears to be facilitated by DHEA; an effective coping predicted higher plasma DHEA levels (Yehuda et al, 2006).…”
Section: Neurobiological Resiliencementioning
confidence: 99%
“…According to the hypothesis the secretion of both cortisol and DHEA-S was expected to develop in a beneficial way as a result of the Shibboleth intervention. There are studies that show that both cortisol (Theorell et al, 2001) and DHEA-S levels could be markedly improved as an effect of interventions aiming to reduce psychological stress or improve psychosocial conditions (Hasson et al, 2005;Johansson & Uneståhl, 2006;Arnetz et al, 1983;McCraty et al, 1998;Antoni, 2003;Carlson et al, 2004).…”
Section: Biological Stressmentioning
confidence: 99%
“…The counteracting inter-balanced secretion towards stress and anxiety of the most numerous androgen DHEA-S has been a suggested force on experience of the positive feeling of wellbeing (Orentreich, Brind, Rizer, & Vogelman, 1984, Boudarene, Legros, & Timsit-Berthier, 2002Normile, 1998). Tentatively, DHEA-S is involved in conditioning of an emotional state based not only on improved wellbeing and external success (Glaser, Brind, Vogelma, Eisner, Dillbeck, Walace, Chopra, Orentreich, 1992;Cawodd & Bancroft, 1996;Johansson & Table 1. SMAE personal trait factors in ice-hockey players.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that the current study explored the lasting effects of mechanical massage and mental training program, as assessments were done at days that participants did not perform the program(s). This study did not focus on the acute or short term effects of the interventions, as the previous studies did (6,9,10). Positive long lasting effects of both mechanical massage and mental training on psychological as well as physiological outcomes have previously been demonstrated (7,8).…”
Section: Effects Of the Stress Intervention Programs On Hrv And Cortisolmentioning
confidence: 98%
“…Another method that has been used to reduce stress is mental training, which teaches people techniques to increase mental relaxation. Evidence on the effectiveness of mental training on physiological stress are scarce, however, one study showed a significant decrease in plasma cortisol in people who participated in a mental training intervention when compared to a control group (6). In a randomized controlled pilot study, the effects of massage therapy and mental training, separately or combined, have been examined in Swedish employees (7,8).…”
Section: Introductionmentioning
confidence: 99%